2020
DOI: 10.1021/acssensors.0c01926
|View full text |Cite
|
Sign up to set email alerts
|

pH-Activatable Cyanine Dyes for Selective Tumor Imaging Using Near-Infrared Fluorescence and Photoacoustic Modalities

Abstract: The full-text file will be made open to the public on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…333 Due to its central role in cancer development, the tumor pH is an important biomarker in cancer that has been exploited for targeted drug delivery and imaging, 339–341 as well as the development of many activatable PA probes. 342–371 Here we highlight some recent examples.…”
Section: Activatable Pa Probesmentioning
confidence: 98%
See 1 more Smart Citation
“…333 Due to its central role in cancer development, the tumor pH is an important biomarker in cancer that has been exploited for targeted drug delivery and imaging, 339–341 as well as the development of many activatable PA probes. 342–371 Here we highlight some recent examples.…”
Section: Activatable Pa Probesmentioning
confidence: 98%
“…A final notable example comes from Miki, Ohe, and coworkers, where the authors reported a pH activatable probe (CypHRGD-C) with PA and fluorescence dual-imaging abilities. 370 This probe exploits an ICG-based pH-sensing platform previously published by the same group. 372 In this design, the cyclization event that results from the mercapto group attacking the central carbon leads to disruption of π-conjugation which attenuates the PA and fluorescent signals.…”
Section: Activatable Pa Probesmentioning
confidence: 99%
“…In the recent 5 years, NIR-I fluorophores in the reported bimodal FI/PAI probes are often served as the CAs of PAI as well. These fluorophores, including natural origin ( Zhou et al, 2017 ; Zheng et al, 2018 ; Siwawannapong et al, 2020 ), cyanine derivatives ( Baart et al, 2021 ; Doan et al, 2021 ; Mu et al, 2021 ; Nishio et al, 2021 ), and other types of organic dyes ( Park et al, 2020 ; Shin et al, 2021 ; Wang et al, 2022 ), had strong and broad optical absorption in the NIR-I region to provide PA signals. Apart from the broad applications of the traditional cyanine dyes, researchers have devoted much attention to developing new structures to obtain better absorption and emission properties in this field.…”
Section: Bimodal Imaging Of Tumor Based On Near-infrared-i Fluorescencementioning
confidence: 99%
“…The rational design of pH‐activable florescent probes should satisfy several parameters: (i) ability to emit high fluorescence at lysosomal acidic pH and negligible fluorescence at cytosolic neutral pH, (ii) cellular permeability and uptake, (iii) non‐specific binding to other cellular components, and (iv) good solubility. Several pH‐activable fluorescent probes contain rhodamine, [5a] coumarin, [5b] naphthalimide, [4b] cyanine [4e–f] and 4,4‐difluoro boron dipyrromethane (known as BODIPY) based scaffolds [5c] . The widely used are BODIPY‐based scaffolds [5d] due to a variety of synthetic routes to introduce diverse functionalities [6a–b] for desired photophysical and spectroscopic properties.…”
Section: Figurementioning
confidence: 99%